The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11356-016-7875-7
|View full text |Cite
|
Sign up to set email alerts
|

Lower tier toxicity risk assessment of agriculture pesticides detected on the Río Madre de Dios watershed, Costa Rica

Abstract: Costa Rica is a tropical country with one of the highest biodiversity on Earth. It also has an intensive agriculture, and pesticide runoff from banana and pineapple plantations may cause a high toxicity risk to non-target species in rivers downstream the plantations. We performed a first tier risk assessment of the maximum measured concentrations of 32 pesticides detected over 4 years in the River Madre de Dios (RMD) and its coastal lagoon on the Caribbean coast of Costa Rica. Species sensitivity distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Alves et al 2013). Arias-Andrés et al (2018) presented specific acute toxicity data with tropical native species (earthworm).…”
Section: Biotic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alves et al 2013). Arias-Andrés et al (2018) presented specific acute toxicity data with tropical native species (earthworm).…”
Section: Biotic Conditionsmentioning
confidence: 99%
“…For example, Bocquené and Franco (2005) found pesticides in water and sediment from rivers in Martinique, Pillai (1986) in soil and air in India, and Dickinson and Lepp (1984) in non-agricultural plants and soils in Kenya. Moreover, Arias-Andrés et al (2018) observed ecotoxicity effects of pesticides on freshwater organisms in Costa-Rica, and Peters et al (1997) on marine organisms in tropical conditions. Pesticides have also been detected in food crops grown in tropical regions, which might exceed the recommended maximum residue limits (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that Oligochaetes, normally very tolerant to low oxygen levels, are only found at upstream sites further supports this conclusion (Fig 2 ). Oligochaetes have been found to be relatively sensitive to fungicides (Cuppen et al 2000 ), which have been found in surface waters downstream banana farms in streams nearby (Castillo et al 2000 ; Diepens et al 2014 ; Arias-Andrés et al 2016 ; Echeverría-Sáenz et al 2016 ; Rämö et al 2016 ). Thus, pesticides used by banana farms may be influencing patterns shown in the biplots presented here (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A major contributor of agrochemicals to the surrounding environment is the large-scale banana production, which receives an average of 57.5 pesticide applications per year as well as 2775 kg/ha of synthetic fertilizers (Bellamy 2013 ; Bravo et al 2013 ). Several of the pesticides used in banana production have been detected in the aquatic environment downstream of banana production areas (Castillo et al 2006 ), some in concentrations expected to have acute or chronic toxic effects on aquatic organisms according to toxicity values derived from laboratory toxicity tests (Diepens et al 2014 ; Arias-Andrés et al 2016 ; Rämö et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the measured environmental concentration (MEC) is compared to the reference sediment values in Löf et al (2016). The MEC-to-reference values ratio is the RQ, and RQ exceeding 1 for a metal suggests that it may pose a toxicity risk to the environment (EFSA, 2013;Arias-Andres et al, 2018). The sum of these RQ values was calculated for each station and used in statistical analyses since all metals correlated significantly and highly to RQ (Pearsons r ≥ 0.90 except for As, Hg and Co, which had values of 0.73-0.89; Supplementary Table 6) and to each other (mean r = 0.80, with only exception being As and Hg, which were not significantly correlated; Supplementary Table 6).…”
Section: Chemical Analysesmentioning
confidence: 99%